An exploration of experiential learning using business simulation and gamification: A case study - Tan, Ru Fu; Zetty Ain, Kamaruzzaman; Zetty Adibah, Kamaruzzaman; Galuh, Tresna Murti (Penerbit UPSI, 2023)
Education with advanced technologies improves the learning of students. Experiential learning prepares students to thrive in today’s digital world. Experiential learning and advanced technologies in education offer a lot of room to be explored. Thus, the objective of this study is to explore the student’s experience in using a business simulation and gamification platform on the student's knowledge of business competency and soft skills. This study also aimed to discover the experiential learning experience using the MonsoonSIM platform as a case study. This study used content analysis and narrative analysis to analyse the results. The focus group interview was carried out with the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) from Gambang and Pekan students who have played MonsoonSIM more than 10 times. The results indicated that business simulation and gamification can improve the students’ knowledge and soft skills by using MonsoonSIM. This study also provided significant implications for experiential learning, business simulation and gamification in the future for Malaysian education.